The Application of Hadhanah Rights for Muallaf Parents and Its Consequences on Child Welfare in Malaysia (An Analysis of Federal Court Decision No. 02-19-2007 (W)): Penerapan Hak Hadhanah Bagi Orang Tua Muallaf dan Konsekuensinya Terhadap Kesejahteraan Anak di Malaysia (Analisis Putusan Mahkamah Persekutuan No. 02-19-2007 (W)) - Hanapi, Agustin; binti Zakri, Nur Afifah; Amalia Jihad, Azka (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2024)
There is a discrepancy between Malaysia's positive law which stipulates that the right to hadhanah (custody) of a child must be given to Muslim parents, and the court ruling that gives non-Muslim mothers the authority to take care of the child. Therefore, there needs to be a deep understanding of how the decision contributes to the best interests of the child and the protection of the child. This article aims to analyze the implementation of hadhanah rights for parents of converts in Islamic family law in Malaysia. This study uses qualitative methods and normative legal approaches, focusing on the Federal Court decision No. 02-19-2007 (W) on the right of hadhanah for parents of converts in Malaysia. Data sources include laws, judges' decisions, and legal literature. Data were collected through literature studies and analyzed inductively. The results of the study show that the Federal Court's decision emphasizes the importance of mutual consent in decision-making related to custody, where the welfare of the child is the top priority. The decision underlines that child protection should include various aspects, such as collaborative custody, emotional well-being, appropriate religious education, and protection from negative influences. Thus, this research contributes to the development of Islamic family law and emphasizes the importance of child protection in the legal system.